Community science data provide evidence for upward elevational range shifts by Eastern Himalayan birds. (28th June 2022) - Girish, Krishna S.; Srinivasan, Umesh
Abstract: The ongoing climate crisis is a significant threat to global biodiversity. As Earth warms, many species respond by shifting their geographical ranges either polewards, or in mountainous regions, upslope towards higher elevations, presumably to track suitable thermal environments. Upslope range shifts are of particular concern in tropical mountain ranges because: (a) tropical species are particularly thermally sensitive; (b) species moving upwards could become locally extirpated as they run out of habitable space; and (c) tropical mountains harbor a high fraction of Earth's terrestrial biodiversity. Rapid upslope shifts can, therefore, result in significant biodiversity losses. We used community science data over a 13‐year period to evaluate whether 93 Eastern Himalayan bird species might be shifting to higher elevations. To do this, we analyzed changes in their occurrence probabilities in eBird checklists from birdwatching hotspots at fixed elevations. We found patterns consistent with upslope range shifts; species with elevational ranges primarily below hotspot elevations show increases in their occurrence probability over time, and those with most of their elevational ranges above a hotspot elevation decline in occurrence probability. Our findings are suggestive of rapid responses to climate change by Eastern Himalayan birds. We caution that Eastern Himalayan bird species might be at special risk from increasing global temperatures because of heightened thermal sensitivity coupled with high rates of warming in the region. To remain resilient in the face of climate change, Eastern Himalayan birds likely require undisturbed habitats spanning entire elevational gradients, to track rising temperatures by moving to higher elevations. Abstract : Montane species are expected to shift their elevational ranges upslope in response to global warming. Using 13 years of community science data on birds from two birding hotspots in the Eastern Himalayas, we analyzed changes in the probability of occurrence for 93 species. Trends from community science data are indicative of upslope range shifts in Eastern Himalayan birds.